INTRASPECIFIC VARIATION IN THE REPRODUCTIVE EFFORT AMONG THREE POPULATIONS OF AN INTERTIDAL GASTROPOD, Nerita japonica (Dunker) - Paruntu, Carolus (Sam Ratulangi University, 2012)
The aim of the present research is to figure out the reproductive effort of Nerita japonica occurring in three different intertidal habitats of Amakusa Shimoshima Island, western Kyushu, Japan. Rocky shore population and other two stony shore populations (the upper stony shore and the lower stony shore) were described based on: (a) its mean mature gonad dry weight, (b) reproductive effort, and (c) the relationship between reproductive effort and body size. Data recorded in the period of spawning season. The results revealed that there were mean mature gonad dry weight and reproductive effort variations among three snail populations. Mean mature gonad dry weight and reproductive effort were larger for the Rocky shore population, intermediate for lower stone shore population, and smaller for the upper stone shore population. In one out of three populations, i.e., the upper stone shore population, reproductive effort of mature females increased significantly with an increase in body size. The data showed that reproductive effort is related to adult body size of N. japonica. There was an intraspecific variation in reproductive effort among three populations of N. japonica over even small geographic distances. Keywords: mature body size, mature gonad dry weight, reproductive effort, intraspecific variation, Nerita japonica. Â Variasi Indeks Kematangan Gonad Interspesies pada Tiga Populasi Gastropoda Intertidal, Nerita japonica (Dunder)) Penelitian ini bertujuan untuk mendeskripsikan indeks kematangan gonad dari gastropoda intertidal, Nerita japonica yang hidup di tiga habitat yang berbeda di Pulau Shimoshima Amakusa, Kyushu bagian barat, Jepang. Parameter yang diamati pada setiap populasi adalah: (a) nilai rata-rata berat kering gonad matang, (b) indeks kematangan gonad, dan (c) hubungan antara indeks kematangan gonad dan ukuran tubuh. Data dicatat pada periode musim pemijahan. Ketiga populasi memperlihatkan nilai rata-rata berat kering gonad yang matang dan indeks kematangan gonad yang berbeda. Populasi pantai berbatu memiliki nilai rata-rata berat kering matang gonad dan indeks kematangan gonad yang paling besar, diikuti oleh nilai dari populasi pantai berbatu bagian bawah dan populasi pantai berbatu bagian atas memiliki nilai yang paling kecil. Selanjutnya, satu dari tiga populasi, yaitu populasi pantai berbatu bagian atas memperlihatkan indeks kematangan gonad dari individu-individu betina N. japonica berhubungan dengan ukuran tubuhnya. Sekalipun indeks kematangan gonad dari individu-individu N. japonica meningkat secara signifikan dengan bertambahnya ukuran tubuh, namun terdapat variasi intraspesifik pada N. japonica dalam hal indeks kematangan gonad menurut habitat walaupun secara geografis berdekatan.Kata kunci: ukuran tubuh matang kelamin, berat kering gonad matang, indeks kematangan gonad, variasi intraspesifik, Nerita japonica.